2019
DOI: 10.1097/ico.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Cross-Linking: The Science Beyond the Myths and Misconceptions

Abstract: Purpose: There has been a recent explosion in the variety of techniques used to accomplish corneal cross-linking (CXL) for the treatment of ectatic corneal diseases. To understand the success or failure of various techniques, we review the physicochemical basis of corneal CXL and re-evaluate the current principles and long-standing conventional wisdom in the light of recent, compelling, and sometimes contradictory research. Methods: Two clinicians and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 158 publications
2
42
0
4
Order By: Relevance
“…Vizzari et al showed that topical application of the antioxidant and shielding solution significantly counteracted the UV-induced oxidative stress in both the aqueous humor and lens of exposed rabbits [40]. Furthermore, riboflavin shows an indirect antioxidant capacity because it has a shielding action (limits the damage caused by UV-A irradiation), as demonstrated in our studies on cross linking [44][45][46].…”
Section: Discussionsupporting
confidence: 71%
“…Vizzari et al showed that topical application of the antioxidant and shielding solution significantly counteracted the UV-induced oxidative stress in both the aqueous humor and lens of exposed rabbits [40]. Furthermore, riboflavin shows an indirect antioxidant capacity because it has a shielding action (limits the damage caused by UV-A irradiation), as demonstrated in our studies on cross linking [44][45][46].…”
Section: Discussionsupporting
confidence: 71%
“…Vizzari et al showed that topical application of the antioxidant and shielding solution significantly counteracts the UV-induced oxidative stress in both aqueous humor and lens of exposed rabbits [40]. Furthermore, riboflavin shows an indirect antioxidant capacity because it has a shielding action (limits the damage caused by the UV-A irradiation) as demonstrated in our studies on cross linking [52][53][54]. The existence of ocular biochemical damages due to acute and chronic exposure to UV-B and UV-A has been widely demonstrated.…”
Section: Discussionsupporting
confidence: 65%
“…If riboflavin degradation is inhibited in the corneal stroma during a clinically relevant time window, ie, over 20–30 min of UVA exposure, 51 then NaI may be helpful to in vivo crosslinking. The data in the present study do not reach statistical significance in showing this independent effect in terms of a decay slope, but do show significantly higher riboflavin grades at 15, 20, and 25 minutes after onset of UVA exposure during crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…After sufficient riboflavin loading, oxygen is the limiting reagent in CXL. [49][50][51] However, with insufficient oxygen UVA radiation photodegrades riboflavin, reducing CXL efficiency 52 and increasing UVA radiation exposure to corneal endothelium. In conventional CXL procedures, effective CXL and endothelial protection is achieved by repeated intraoperative application of riboflavin onto a deepithelialized stromal surface.…”
Section: Introductionmentioning
confidence: 99%